Our “energy-Ca2+ signaling deficits” hypothesis and its explanatory potential for key features of Alzheimer’s disease - Chen, Ming; Nguyen, Huey T. (Frontiers in Aging Neuroscience, 2014)
Alzheimer’s disease (AD) has not been explained by any current theories, so new hypotheses are urgently needed. We proposed that “energy and Ca2+ signaling deficits” are perhaps the earliest modifiable defects in brain aging underlying memory decline and tau deposits (by means of inactivating Ca2+-dependent protease calpain). Consistent with this hypothesis, we now notice that at least eight other known calpain substrates have also been reported to accumulate in aging and AD. Thus, protein accumulation or aggregation is not an accidental or random event, but occurs naturally and selectively to a peculiar family of proteins, corroborating the proposed changes of calpain. Why are only calpain substrates accumulated and how can they stay for decades in the brain without being attacked by many other non-specific proteases there? We believe that these long-lasting puzzles can be explained by calpain’s unique properties, especially its unusual specificity and exclusivity in substrate recognition, which can protect the substrates from other proteases’ attacks after calpain inactivation. Interestingly, the energy-Ca2+ deficits model, in essence, may also explain tau phosphorylation (by calcineurin inactivation) and the formation of amyloid plaques. Our studies suggest that α-secretase is an energy-/Ca2+-dual dependent protease and is also the primary determinant for Aβ levels. Finally we discuss why “β- and γ-secretases”, the current enthusiastic study focuses, are unlikely to be responsible for Aβ genesis or be “positively identified” by biological laws. Overall, the study suggests that our hypothesis can coherently explain several basic AD features, thus pointing to a new strategy for AD prevention.